Consolidated Treasury from a cash flow and traditional indicators from an analytical point of view -Case study of the GROUPE SAIDAL for the period 2011-2015- (Journal of Economic Additions, 2020)
This study aims at analyze the consolidated treasury of the GROUPE SIDAL for the period 2011-2015 based on the financial ratios derived from the table of the combined treasury flows, the traditional indicators derived from the budget and the consolidated results table, Based on the descriptive analytical method, and to know which indicators are the most efficient and accurate in the analysis process, Financial statements of the compound under study. The study concluded by analyzing the cash flow ratios and the traditional indicators that the compound achieved a good financial position throughout the study period, although there is some fluctuation in growth rates and return to fluctuations in turnover growth rate, and that the analysis process has shown us the degree of integration Between the cash flow ratios and the traditional indicators, so that the cash flow ratios cannot be relied upon independently to explain the financial position of the complex under study, Rather, the analysis should be emphasized by the financial ratios derived from the flow table in addition to the traditional indicators.Keywords:  Consolidated Treasury; Cash Flow; Traditional Indicators; Net Result; Turnover;